Interview with Beatrice Janzon, Swedish Radio International - Malpass, David (World Bank, Washington, DC, 2021)
David Malpass, President of the World Bank, discussed with Beatrice Janzon, Swedish Radio International, the following topics: long-term effects of children out of school during the pandemic, economic recovery for developing countries, importance of vaccinations for the developing countries, and World Bank on Paris Agreement on Climate Change.